Mycoplasma genitalium adhesin P110 binds sialic-acid human receptors. Issue 1 (December 2018) - Aparicio, David; Torres-Puig, Sergi; Ratera, Mercè; Querol, Enrique; Piñol, Jaume; Pich, Oscar; Fita, Ignacio
Abstract Adhesion of pathogenic bacteria to target cells is a prerequisite for colonization and further infection. The main adhesins of the emerging sexually transmitted pathogenMycoplasma genitalium, P140 and P110, interact to form a Nap complex anchored to the cell membrane. Herein, we present the crystal structures of the extracellular region of the virulence factor P110 (916 residues) unliganded and in complex with sialic acid oligosaccharides. P110 interacts only with the neuraminic acid moiety of the oligosaccharides and experiments with human cells demonstrate that these interactions are essential for mycoplasma cytadherence. Additionally, structural information provides a deep insight of the P110 antigenic regions undergoing programmed variation to evade the host immune response. These results enlighten the interplay ofM. genitalium with human target cells, offering new strategies to control mycoplasma infections. How theMycoplasma genitalium cytadhesins P140 and P110 promote host cell invasion remains poorly understood. Here, combining structural analysis with functional assays, Aparicio et al. identify the P110 domain that binds to sialylated receptors essential for mycoplasma cytadherence.